Tribological behaviour of Si3N4–BN ceramic materials for dry sliding applications - Carrapichano, J. M. (2002)
The main objective of this paper is to help on the clarification of the lack of consensus in the bibliographic data concerning the tribological behaviour of Si3N4–BN omposites. Unlubricated sliding tests by pin-on-disc were carried out with three grades of composite materials with 10, 18 and 25 vol.% of BN. The addition of BN to the Si3N4 matrix resulted in a slight reduction of the friction coefficient, which decreased from 0.82 for monolithic Si3N4 to 0.67 for Si3N4–10%BN materials. Wear coefficients (K) were above 10−5 mm3 N−1 m−1 for all materials tested and increased sharply with increases in BN volume fraction greater than 10%, e.g. K ∼ 10−3 mm3 N−1 m−1 for Si3N4–25%BN. The lowest values of friction and wear coefficients were obtained when the composites were tested with the BN platelets oriented parallel to the sliding direction. The morphological study of the worn surfaces revealed generalised brittle intergranular icrocracking at the dispersoid/matrix interface as the main wear mechanism. Under the experimental conditions of this study, the formation of stable protective layers of the soft lubricious oxide H3BO3, or the solid lubricant BN·H2O, was not observed.